PENGARUH JUMLAH MAHASISWA TERHADAP ANGGARAN DIVISI PENDIDIKAN PROFESI GURU DAN JASA KEPROFESIAN UNIVERSITAS PENDIDIKAN INDONESIA - Rahmat, Rahmat Hidayat; Euis Hernawati (JEBS (Journal of Economic and Business Student), 2023)
This study aims to determine the effect of the number of students on the budget for teacher professional education and professional services at the Indonesian Education University using quantitative methods. The statistical method carried out by the author is SPSS version 26 with the Pearson Product Moment method. The results showed a significance of 0.002 <0.05, which means that there is a correlation between the number of students and the budget. The amount of influence between the number of students and the author’s budget uses the coefficient of determination (R square) method with a result of 83.4%. From the results of the T-test, which show that Thitung is 5.489> Ttable of 2.447, it can be concluded that the number of students has a significant influence on the budget, which can prove the hypothesis that has been made by the author. The obstacles in this study are the increasing number of students and the budget in 2020, which are caused by the number of students who are not on time in conducting college studies. Efforts to deal with these obstacles are to provide motivation to students so that they are on time for college study activities and use other activity budget posts to cover the excess budget for PPLSP activities.